2018
DOI: 10.1016/j.neuroimage.2017.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Neural and metabolic basis of dynamic resting state fMRI

Abstract: Resting state fMRI (rsfMRI) as a technique showed much initial promise for use in psychiatric and neurological diseases where diagnosis and treatment were difficult. To realize this promise, many groups have moved towards examining "dynamic rsfMRI," which relies on the assumption that rsfMRI measurements on short time scales remain relevant to the underlying neural and metabolic activity. Many dynamic rsfMRI studies have demonstrated differences between clinical or behavioral groups beyond what static rsfMRI m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 209 publications
(310 reference statements)
3
34
0
Order By: Relevance
“…Although unreported so far, the match between dFC states derived from fMRI and EEG data found in the present study was somewhat expected, considering that a number of studies have already found EEG correlates of dFC fluctuations and brain states measured with simultaneous fMRI (Tagliazucchi and Laufs, 2015), motivated by the yet unclear physiological underpinnings of dFC (Thompson, 2018). These studies were mainly focused on healthy subjects (Chang and Glover, 2010;Allen et al, 2017) and epilepsy patients (Laufs et al, 2014;Lopes et al, 2014;Preti et al, 2014;Omidvarnia et al, 2017;Abreu et al, 2019).…”
Section: Dynamic Functional Connectivity and Brain Statessupporting
confidence: 70%
See 2 more Smart Citations
“…Although unreported so far, the match between dFC states derived from fMRI and EEG data found in the present study was somewhat expected, considering that a number of studies have already found EEG correlates of dFC fluctuations and brain states measured with simultaneous fMRI (Tagliazucchi and Laufs, 2015), motivated by the yet unclear physiological underpinnings of dFC (Thompson, 2018). These studies were mainly focused on healthy subjects (Chang and Glover, 2010;Allen et al, 2017) and epilepsy patients (Laufs et al, 2014;Lopes et al, 2014;Preti et al, 2014;Omidvarnia et al, 2017;Abreu et al, 2019).…”
Section: Dynamic Functional Connectivity and Brain Statessupporting
confidence: 70%
“…In contrast with the identification of RSNs, whereby templates derived from previous fMRI studies of large populations are available, dFC state templates are yet to be discovered, as this is still a fairly recent research topic (Preti et al, 2017;Thompson, 2018). Thus, the dFC states estimated from the EEG-ESI data can only be cross, rather than independently, validated by the dFC states estimated from the fMRI data.…”
Section: Matching Of Eeg-esi and Fmri Dfc Brain Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, some studies have found that impaired cognitive function is related to altered functions in specific regions -such as the precuneus, anterior cingulate cortex, and medial precentral gyrus (Bruner et al, 2017) -and those depressive symptoms are related to aberrant functioning in some brain networks, such as the fronto-parietal network and default mode network (DMN) (Korgaonkar et al, 2019). Recently, dynamic functional activity and connectivity analyses have been used to measure temporal flexibility in spontaneous fluctuations (Thompson, 2018). The major advantage of dynamics over static measures is the ability to capture recurring brain activity (Xie et al, 2018), and specific exploration of dynamics may complement deficiencies in static alterations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, based on the premise that BOLD fMRI signal variability reflects neural variability as measured by rsEEG, we expected that the corresponding changes in both signal modalities would demonstrate moderate to strong similarity in their spatial distribution. Given the confounding effects of vascular factors during aging on the fMRI signal (D'Esposito et al, 2003;Liu, 2013;Thompson, 2018), we further expected to find the relationship between BOLD and EEG signal variability to be stronger in younger than older adults.…”
Section: Introductionmentioning
confidence: 99%